STRATEGI PARENTING DI ERA DIGITAL: ORANGTUA SEBAGAI MEDIATOR DALAM PENGGUNAAN MEDIA DIGITAL - T. AFRIWILDA, MAYANG; Indrajati Kunwijaya (UNIVERSITAS BENGKULU, 2022)
Technological developments are unavoidable. In this digital era, technology has become an integral part of our daily life. This brings changes in many ways, one of which is the life experience of early childhood in the present era. The digital era has both positive and negative impacts. As a step so that children do not get the negative impact of this technological development, parents as the closest people must be able to apply appropriate parenting strategies in the digital era. There are several strategies that parents can apply in early childhood education in the digital era which will be discussed in this article. It is hoped that parents can implement this strategy in order to minimize the negative impact of using digital media.